Weed seed germination and the light environment. Implications for weed management - Batlla, Diego (2014)
Light regulates dormancy termination and the subsequent germination in many weed species. Under field conditions, the light environment of the seeds, which is perceived mainly by photoreceptors of the phytochrome family, provides essential information for cueing germination in the proper environmental situation. The light environment?s spectral composition and irradiance allow weed seeds to sense their position in the soil profile, the presence of a leaf canopy capturing light and other resources and the occurrence of soil cultivation. From an agronomical point of view, the control of germination by light represents a potentially useful step in the life cycle of weeds for developing effective control practices. The goal of this article is to place current knowledge regarding photoreceptors, physiological and molecular bases of seed responses to light and their ecological implications within the context of weed management in agricultural systems. With that final objective, the authors intend to show how a better understanding of the way in which the light environment regulates dormancy termination and the subsequent germination of weed seeds could be used to develop more accurate control practices and to improve weed management strategies.